9(u-1)=6u-24

Simple and best practice solution for 9(u-1)=6u-24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(u-1)=6u-24 equation:


Simplifying
9(u + -1) = 6u + -24

Reorder the terms:
9(-1 + u) = 6u + -24
(-1 * 9 + u * 9) = 6u + -24
(-9 + 9u) = 6u + -24

Reorder the terms:
-9 + 9u = -24 + 6u

Solving
-9 + 9u = -24 + 6u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-6u' to each side of the equation.
-9 + 9u + -6u = -24 + 6u + -6u

Combine like terms: 9u + -6u = 3u
-9 + 3u = -24 + 6u + -6u

Combine like terms: 6u + -6u = 0
-9 + 3u = -24 + 0
-9 + 3u = -24

Add '9' to each side of the equation.
-9 + 9 + 3u = -24 + 9

Combine like terms: -9 + 9 = 0
0 + 3u = -24 + 9
3u = -24 + 9

Combine like terms: -24 + 9 = -15
3u = -15

Divide each side by '3'.
u = -5

Simplifying
u = -5

See similar equations:

| 2x^2-x-36= | | 24.50+2(24.50+3)+(424.50-5)=148 | | Y-2=4/7(x-3) | | 10-7=20-n | | -3/10н=15 | | 19+10x+1=90 | | 9x^2+12xy+4y^2-25=0 | | 45=14t+16t | | 4x^2+48x-28=0 | | 32k-435=179 | | 15x+12=20x-8 | | 4y-4x=8 | | 4/v=8 | | x-40+.75x=180 | | 6x^2-2x=18 | | F(x)=x^3+2x^2-9x-18 | | 5x-(1414-x)=-30-2x | | (2x+12)(2x+18)=216 | | 7+21ln=4 | | 112=-4(5n-4)+4n | | (9x/5)-12 | | -13x-12=-(1+x)-12(x+3) | | 15(k+1)=-4 | | x-40+3x=180 | | 9x/5-12 | | 15x-2(10+5x)=2 | | 90+7x=139 | | 40+37=3x-13 | | 12x-5=4(2x-15) | | -7m+10m+11=-7 | | x^2-11x-2420=0 | | -19u=2u+9-6u |

Equations solver categories